Dithienylthienothiophenebisimide, a Versatile Electron‐Deficient Unit for Semiconducting Polymers. Issue 32 (23rd May 2016) - Saito, Masahiko; Osaka, Itaru; Suda, Yosuke; Yoshida, Hiroyuki; Takimiya, Kazuo
Abstract : A novel electron‐deficient building unit, dithienylthienothiophenebisimide, and its polymers (PTBIs) are reported. Organic photovoltaic (OPV) cells based on PTBIs as p‐type material exhibit 8.0% efficiencies with open‐circuit voltages higher than 1 V. Interestingly, PTBIs also function as n‐type material in OPVs depending on the molecular structure. These polymers also exhibit p‐channel, n‐channel, and ambipolar behaviors in field‐effect transistors.